2003
DOI: 10.1038/sj.leu.2403112
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic triterpenoids activate a pathway for apoptosis in AML cells involving downregulation of FLIP and sensitization to TRAIL

Abstract: Acute myelogenous leukemia (AML) remains a deadly disease for most adult patients, due primarily to the emergence of chemoresistant cells. Defects in apoptosis pathways make important contributions to chemoresistance, suggesting a need to restore apoptosis sensitivity or to identify alternative pathways for apoptosis induction. Triterpenoids represent a class of naturally occurring and synthetic compounds with demonstrated antitumor activity, including 2-cyano-3,12-dioxoolean-1,9-dien-28-oic acid (CDDO) and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
70
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 34 publications
3
70
0
Order By: Relevance
“…Because overexpression of these proteins has been shown to contribute to TRAIL resistance in tumor cells (9,45,46), it is likely that the sensitization of tumor cells to TRAIL is due to down-regulation in the expression of cell survival proteins by azadirone. In agreement with our observations, previous studies have shown that triterpenes such as nimbolide (37), celastrol (40), and 2-cyano-3,12-dioxoolean-1,9-dien-28-oic acid (CDDO) (47) can sensitize tumor cells to TRAIL by suppressing expression of cell survival proteins. XIAP, a potent inhibitor of caspase-3 activity, has previously been shown to confer resistance to TRAIL (48).…”
Section: Discussionsupporting
confidence: 81%
“…Because overexpression of these proteins has been shown to contribute to TRAIL resistance in tumor cells (9,45,46), it is likely that the sensitization of tumor cells to TRAIL is due to down-regulation in the expression of cell survival proteins by azadirone. In agreement with our observations, previous studies have shown that triterpenes such as nimbolide (37), celastrol (40), and 2-cyano-3,12-dioxoolean-1,9-dien-28-oic acid (CDDO) (47) can sensitize tumor cells to TRAIL by suppressing expression of cell survival proteins. XIAP, a potent inhibitor of caspase-3 activity, has previously been shown to confer resistance to TRAIL (48).…”
Section: Discussionsupporting
confidence: 81%
“…26 In AML cells, synthetic triterpenoids activate a pathway for apoptosis involving downregulation of Flip and sensitization to TRAIL. 27 We found a downregulation of Flip with a cleavage 38 kDa Flip in K562 cells, but not in HL60 cells. We propose a different mechanism of apoptosis induced by VPA.…”
Section: Discussionmentioning
confidence: 75%
“…CDDO induces apoptosis through both caspase-independent and -dependent mechanisms, the latter involving caspase-8 activation, Bid cleavage, cytochrome c release, and caspase-3 activation. [3][4][5][6] Furthermore, JNK, p38, and ERK pathways are involved in CDDO-induced apoptosis of tumor cell lines [7][8][9] mediated by disrupted intracellular redox balance and involving decreased glutathione and increased reactive oxygen species [9][10][11][12] CDDO-induced growth arrest of breast cancer cell lines correlates with transactivated PPARgamma and leads to up-regulation of p21 cip1waf1 , GADD153, CCAAT enhancer-binding proteins (CEBPs), and proteasome-regulatory factors, and to down-regulation of cyclin D1, PCNA, and IRS1. 13 CDDO and CDDO-Im activate the TGF␤ pathway through activation of Smad2/3, 14,15 which is required for the repression of inflammatory molecules by CDDO.…”
Section: Introductionmentioning
confidence: 99%